Factors that contribute to tendency into truancy among upper level students in SMK Merbok, Kedah / Mohd Akram Mat Jusoh and Nurul Fatin Iffah Mansor - Mat Jusoh, Mohd Akram; Mansor, Nurul Fatin Iffah (2019)
Chapter 1 explained about the research background and problem statement of the tendency into truancy among upper level students. Then, this chapter also identified the research questions on specific factors that contribute to the problem of truancy. In addition, this chapter also contained the research objectives where to show the objectives of this study that need to be achieve and also to ensure that this study have key success. Next, in the scope of study explained about the timeframe, territory and level that the researchers chose to conduct this study. Moreover, the significance of the study explained in order to identify the target group that would benefited from this study. Lastly, the definition of term, terminologies and concept that used in this study also explained in this chapter to ensure the understanding of the audiences.